Flow Injection Analysis Nitrite Sensor Based on Reduced Graphene Oxide Modified Electrode - Nurulasma, Zainudin; M. M., Yusoff; K. F., Chong (Trans Tech Publications, Switzerland, 2015)
Nitrite is one of the most frequently measured analytes in the environmental analysis due to its detrimental effect on the environment. The development of simple and sensitive analytical method for the detection of nitrite is highly important. In this study, we report the fabrication and testing of nitrite sensor based on the flow injection analysis by reduced graphene oxide modified electrode. The modified electrode exhibits enhanced electro oxidation behavior towards nitrite oxidation. The proposed method has advantages of high precision, lower sample consumption, lower reagent consumption, less dispersion of the sample as well as higher sensitivity.